Maintenance of roof - space frame structure (case study: Pusat Akuatik Darul Ehsan and Matsushita Sport Centre Shah Alam Selangor) / Fakruzaman Ab.Rahim - Ab.Rahim, Fakruzaman (2002)
Roof system used space frame technique is most sophisticated of architectural form. As you know the cost of construction is very high compare to another type of roof structure. Also from that, the maintenance work of that structure is very high, if involved of replacement space frame itself. Therefore all inspection job and corrective job should be following specification instruction. All defects will be decrease if all parties involved during construction stage allowing a good planning which as design scope. Moreover less of concerning in maintenance has make the design consideration failed. The awareness in using materials to meet the effect of deterioration is not to be accounted because they are only thinking about the beautiful and attractive of design. This dissertation would focus on defect occurring at roof system using roof structure space frame. Also covers whatever type of defect was found at that roof system. From that try justified that type of defect whether minor defect of major defect. Apart from study also covers about to provide the maintenance guide before inspection will to do. That meant, the inspection should be know about maintenance guide before any inspection will carry on. In actual phenomena, all factor related how to decrease of defect occurred will come out by recommendation and conclusion last of all